(untitled) (American Journal of Islam and Society, 2025)
This paper explores the evolution of the national identity of Bosnian Muslims throughout the 20th century, from an Ummatic-centric focus on their Islamic identity (using the ethnonym “Muslims”) to a state-centered, secularized, and “modernized” identity, adopting the ethnonym “Bosniacs.” This shift is framed as necessary for the biological, religious, and cultural preservation of Bosnian Muslims. The study builds on Bosnian sociologist Sacir Filandra’s typology of the Bosniac national renaissance (Preporod), which he divides into three phases. The most recent phase emphasizes statehood, while earlier phases focused on religious preservation (during the Hapsburg/Ottoman and Yugoslav monarchy eras) and nationhood (under Communism). Filandra links this third phase to Alija Izetbegovic’s political movement, which spearheaded the broader Bosniac mobilization for statehood. Izetbegovic’s “Party for Democratic Action” is seen as the primary driver of this national struggle within the post-Communist political system. The paper provides a historical overview of how Bosnian Muslims transitioned from being part of the Ummah to identifying as Bosniacs tied to a nation-state, alongside an analysis of the Ummatic implications of this transformation.